ANALISIS PENERAPAN PARADIGMA E-GOVERNMENT PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN PESISIR SELATAN - Hazid Jalma; Desna Aromatica; Ria Ariany (Politeknik STIA LAN Makassar, 2022)
E-government is a milestone for the government's use of information technology, requiring bureaucrats to shift from a bureaucratic paradigm to an e-government paradigm in order to effectively utilize information technology. This study intends to describe the implementation of the e-government paradigm at the Pesisir Selatan District Department of Communication and Information Office. Observation, interviews, qualitative documentation materials with personnel and stakeholders of the Communication and Information Office of Pesisir Selatan District are utilized to collect descriptive qualitative data. Several research indicators, including orientation, organizational processes, management principles, leadership style, internal communication, external communication, and the service delivery, indicate that the implementation of an electronic-based government system by the Department of Communication and Information Office of Pesisir Selatan District has utilized the e-government paradigm. This study concludes that the implementation of the e-government paradigm in the implementation of an electronic-based government system by the Communication and Information Office Pesisir Selatan District has a positive effect on government-held public services, the process of completing tasks through the use of technology, and the relationship between stakeholders and the Communication and Information Office Pesisir Selatan District.